The Empirical Research of The Potential, Awareness and Current State of Agricultural Waste Use to Ensure Energy Autonomy of Agricultural Enterprises of Ukraine - PRYSHLIAK, Natalia; LUTSIAK, Vitaliy; TOKARCHUK, Dina; SEMCHUK, Iryna (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020, 2020)
Today, the issues of waste management are complex, because they relate to various aspects – resource conservation, environmental safety of mankind, ensuring competitiveness at micro, macro and mega-levels. The study is devoted to the analysis of the potential, awareness and current state of use of agricultural waste to ensure energy autonomy of agricultural enterprises of Ukraine on the basis of the experimental study, conducted by the authors using a mixed method. The main tool in the study was the survey developed by the authors, which was filled out by the owners of agricultural enterprises in Ukraine. The development of the survey was accompanied by the authors' hypotheses regarding the need for energy autonomy of agrarian enterprises; main sources of information on opportunities and state support for energy use of waste; potential and current state of bioproduction in agrarian formations. Authors acknowledged that both the crop and livestock industries lead to the generation of waste that has the potential to produce biofuels (solid – pellets, briquettes; gaseous – biogas). The study confirmed that the costs for providing agrarian enterprises themselves with fuel and energy resources in Ukraine are quite high, and the bioenergy potential of waste to replace traditional energy resources is practically not used. Further studies will cover a range of questions regarding the extension of the geography of the survey to the whole territory of Ukraine, the specification of hypotheses based on the preliminary questionnaire, the hypothesis testing and the correlation between different indicators of the agrarian waste potential for biofuel production and the efficiency of substitution of traditional energy with biofuels.